Efficient and stable mixed perovskite solar cells using P3HT as a hole transporting layer. Issue 21 (18th May 2018) - Zhou, Peng; Bu, Tongle; Shi, Shengwei; Li, Lingfeng; Zhang, Yulong; Ku, Zhiliang; Peng, Yong; Zhong, Jie; Cheng, Yi-Bing; Huang, Fuzhi
Abstract : Dopant-free P3HT was employed as hole transport materials for stable mixed perovskite planar solar cells. Abstract : Inorganic–organic hybrid perovskite solar cells (PSCs) have drawn great attention in the past several years. As the stability of PSCs has been a major obstacle for their commercialization, a lot of work has been focused on improving the long-term stability. Here, we reported a meso-structured mixed PSC employing poly(3-hexylthiophene-2, 5-diyl) (P3HT) as a hole transport layer (HTL) showing a stable performance even after one year of exposure to air. The impact of different HTL thicknesses on the power conversion efficiency (PCE) of the PSCs has been investigated. The performance of the PSCs was further improved by doping Li-salt/4- tert -butylpyridine into the P3HT HTL. A maximum PCE of 17.55% was achieved, superior to the 14.30% PCE of the pristine P3HT-based devices. The effect of the dopants on the stability of the devices has also been studied.